WHAT MAKES THE PRONOUN “DIO” IN UPSTREAM JAMBI AND PALEMBANGNESE SO SPECIAL? - Bambang Kartono (Kelasa, 2017)
AbstractChomsky’s Canonical Binding Theory (CBT) argues that pronouns cannot be bound in the localdomain, however a locally bound pronominal occurs in Frisian. The CBT with its binary featurescannot explain why the pronoun him in Frisian can occupy a reflexive position without violatingPrinciple B. The same phenomenon of a locally bound pronoun can also be found in Jambi andPalembangnese. The pronoun dio in these languages allows a reflexive interpretation. This papertries to argue what makes the pronoun dio can be bound in the local domain. It might be the casethat dio in these two languages is more like the pronoun him in Frisian, but an alternativeexplanation may also exist. The result of the analysis shows that the pronoun dio has a differentcase compared to the pronoun him in Frisian. The pronoun dio in Upstream Jambi andPalembanese can have a reflexive interpretation due to the phi-features it carries. The pronoundio is not specified for features of number. This difference reflects the crucial determinationwhether the pronoun can be locally bound or not. AbstrakCanonical Binding Theory (CBT) dari Chomsky menyatakan bahwa pronomina tidak dapat diikatdalam domain lokal, akan tetapi pronomina tersebut dapat ditemukan di bahasa Frisian. CBTdengan fitur binarinya tidak dapat menjelaskan mengapa pronomina him dalam bahasa Frisiandapat menempati posisi refleksif tanpa melanggar Prinsip B dari CBT. Fenomena yang sama untukpronomina yang dapat diikat di domain lokal dapat ditemukan juga di bahasa Palembang danJambi. Pronomina dio di bahasa tersebut dapat memperkenankan interpretasi refleksif. Tulisan inimencoba mengemukakan apa yang membuat pronomina dio dapat diikat di domain lokal.Mungkin saja kasus pronomina dio sama seperti kasus pronomina him dalam bahasa Frisian,tetapi penjelasan alternatif lainnya mungkin saja ada. Hasil analisis menunjukkan bahwapronomina dio memiliki penjelasan yang berbeda dibandingkan pronomina him dalam bahasaFrisian. Pronomina dio dalam bahasa Palembang dan Jambi dapat memiliki interpretasi refleksifkarena phi-features yang dibawanya. Pronomina dio tidak terspesikasi untuk fitur jumlah.Perbedaan ini memberikan penentuan yang krusial apakah sebuah pronomina dapat diikat dalamdomain lokal atau tidak.